Pendampingan Dan Penerapan Media Cerita Bergambar Dwibahasa Indonesia-Jerman Untuk Pencegahan Perundungan Anak,Tk Islam Al Ikhlas Taqwa Medan Area, Kota Medan - Rina Evianty; Srinahyanti Srinahyanti; Risnovita Sari; Nurhanifah Lubis; Salmah Naelofaria (Jurnal Gema Ngabdi, 2026)
Bullying in early childhood may hinder children’s social, emotional, and psychological development; therefore, prevention strategies should be aligned with their learning characteristics. This community service program aimed to improve teachers’ ability to use Indonesian–German bilingual picture-story media and strengthen prosocial behavior among children at Al Ikhlas Taqwa Islamic Kindergarten, Medan. The program employed a Participatory Action Approach consisting of program socialization, teacher training, four weeks of classroom mentoring, and evaluation. Observations showed that teasing decreased by 50%, peer exclusion by 58%, and unwillingness to share by 53%. Teachers’ knowledge scores increased from 58 to 87, while children were able to use at least three German social expressions. Bilingual picture-story media effectively supported bullying prevention, promoted polite communication, and introduced a foreign language in an engaging manner. The program can be sustained through regular storytelling activities and the continued development of similar educational media.